Tattooing and piercing are associated with symptoms of ADHD: A cross-sectional study of non-clinical adults - M. Glans; S. Bejerot; J. Dossou Nilsson (European Psychiatry, 2022)
Introduction Previous studies suggest that individuals with tattoos and piercings exhibit higher impulsive personality traits compared to peers without body modifications. No studies on body modifications and core-symptoms of ADHD are available.